Expression of the argA Gene Carried by a Defective Lambda Bacteriophage of Escherichia coli - Leisinger, Thomas (1976)
Evidence is presented that the increase in specific activity of N-acetylglutamate synthase observed upon heat induction of Escherichia coli (λdargA) is primarily due to a gene dosage effect.